Malaysian political parties’ roles in enhancing women’s agenda: a case study of the 14th general election manifestos - Aminudin, Rabi'ah; Sharif, Megat Muhammad Syamil; Ahmad, Nadzrah (Institut Sosial Malaysia, 2020)
This paper aims to analyze the role of Malaysian political parties in enhancing women’s agendas through their election manifestos. This study analyses political parties’ election manifestos in the Malaysian 14th General Election in 2018 using the gender policy matrix. It identifies that political parties have included women’s agendas in their manifestos to attractmore female voters. The study also finds large differences among political parties in terms of numbers and types of women’s agendas included in their election manifestos. This paper proposes that political parties need to improve on their gender cards, especially considering that women make up 49 percent of the Malaysian population. The lack of female agendas in their manifestos indicates the absence of political will to address female related issues.